Attenuation of microbial-induced deterioration of cellu-lose fibers by hornwort (Ceratophyllum demersum L.) methanolic extract - Mohamedomar, Ali; Salah, Ayman Taha; Mohamed, Amal A. A.; Sheded, Mohamed G. (International Journal of Biological Research, 2017)
Plants are endowed by a variety of secondary metabolites, which have potent antimicrobial activity to treat vulnerable subjects against microbial-induced damage. In this study, bacteria and fungi were isolated from the infected manuscript dated back to 8th century AHkeptatAl-Azhar library in Cairo, Egypt. The material of that manuscript was made from cellulose fibers.Three bacterial species, Bacillus subtilis, Bacillusmegatrium and Streptomyces spanned five fungal species, Aspergillusnispecies. Aspergillusniger, The antibacterial and antifungal activities of methanolic extracts of stems and leaves of Ceratophyllumdemersum were evaluated using agar well diffusion technique. The results showed remarkable inhibition ingrowth of isolatedbacteria and fungitreated with the plant extracts.In addition, treating of the modern Ractapapers with Ceratophy llumdemersum extracts resulted in ameliorating physical and mechanica lproperties of the papers. Moreover, against microbial attack of Racta papers was increased after treating with Ceratophy llumdemersum extract.